2002
DOI: 10.1046/j.1460-9592.2002.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Conduction Properties of the Crista Terminalis and Its Influence on the Right Atrial Activation Sequence in Patients with Typical Atrial Flutter

Abstract: The conduction properties of the crista terminalis (CT) and its influence on the right atrial activation sequence were analyzed in 14 patients with typical atrial flutter (AF). Atrial mapping was performed with 35 points of the right atrium during typical AF and during atrial pacing performed after linear ablation of inferior vena cava-tricuspid annulus (IVC-TA) isthmus. Atrial pacing was delivered from the septal isthmus at cycle lengths of 600 ms and the tachycardia cycle length (TCL). The right atrial activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…7,8 Thus, there may be the complication of another loop reentry, together with typical AFL rotation around the TA. Furthermore, the other loop reentry would travel across the line between the SVC and IVC in the posterolateral wall of the RA, and this has been confirmed by conventional electrophysiological methods, 9 electroanatomic mapping 10 and, recently, by noncontact mapping. 7,8 The pattern of propagation across the posterolateral RA has been studied using virtual electrograms, 8 but the conduction patterns and conduction velocity (CV) across the CT during typical AFL, as seen on actual electrograms, are not completely understood.…”
mentioning
confidence: 78%
“…7,8 Thus, there may be the complication of another loop reentry, together with typical AFL rotation around the TA. Furthermore, the other loop reentry would travel across the line between the SVC and IVC in the posterolateral wall of the RA, and this has been confirmed by conventional electrophysiological methods, 9 electroanatomic mapping 10 and, recently, by noncontact mapping. 7,8 The pattern of propagation across the posterolateral RA has been studied using virtual electrograms, 8 but the conduction patterns and conduction velocity (CV) across the CT during typical AFL, as seen on actual electrograms, are not completely understood.…”
mentioning
confidence: 78%
“…[4][5][6] Most former studies assumed that the localization of the transverse conduction block was the CT in AFL patients. [4][5][6][7][8][9] However, more current studies [14][15][16][17][18] using ICE or noncontact mapping systems have concluded that the conduction block occurred at the posteromedial RA (sinus venosa region) rather than on the CT. The present study also showed that the DP recording site observed in the AFL patients was located at the posterolateral RA adjacent to the posterior edge of the CT or posteromedial RA.…”
Section: Localization Of the Transverse Conduction Block And Electropmentioning
confidence: 99%
“…The prior studies [6][7][8][9]20,21 showed a rate-dependent conduction block at the posterior RA and a propensity for conduction block in AFL patients as compared with those with atrial fibrillation. 6,7,9 In the present study, the ERP of the posterior RA was also significantly longer in the AFL patients than in the control patients.…”
Section: Localization Of the Transverse Conduction Block And Electropmentioning
confidence: 99%
See 2 more Smart Citations